E-Vote Menggunakan RFID Sebagai Login Key Untuk Pemilihan Ketua Organisasi Universitas Kristen Petra Berbasis Web - Daniswara Kusuma Aji; Justinus Andjarwirawan; Alexander Setiawan (Jurnal Infra, 2019)
Voting or more commonly called voting is one method that is used by humans to make choices, decisions in a matter. In Indonesia alone voting is often used in the election of leaders such as the president, student council president and at the head of the organization. In the election in Petra itself there were many problems such as ballot paper folds for voting, long time duration on vote preparation and vote counting. In this case, the most affected by this problem is the election committee because it takes a long time and preparations with a lot of labor needs have not been added to by human error which can cause loss to many parties. It can be concluded that the problem is how to vote by using paper that is efficient and does not take a long time and how everyone only makes one vote once.To answer this problem, an electronic voting system was designed using rfid and also website-based thermal printer and barcode technology. By using this technology, each voter will get a receiptthat will be entered into the ballot box so that it can be re-audited if needed. In addition, this resolves the problem of inefficient paper use and reduces the burden on the election committee. voting must be regisified first and will be checked whether the voter has voted or not.